2002
DOI: 10.1074/jbc.m201875200
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-1 Activation of c-Jun N-terminal Kinase and AP-1 Is Mediated by Heterotrimeric G Proteins

Abstract: Functional analysis of polycystin-1, the product of the gene most frequently mutated in autosomal dominant polycystic kidney disease, has revealed that this protein is involved in the regulation of diverse signaling pathways such as the activation of the transcription factor AP-1 and modulation of Wnt signaling. However, the initial steps involved in the activation of such cascades have remained unclear. We demonstrated previously that the C-terminal cytosolic tail of polycystin-1 binds and activates heterotri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
177
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(185 citation statements)
references
References 66 publications
3
177
3
2
Order By: Relevance
“…We propose that polycystin-1 is capable of inducing at least c-Jun and ATF2 activity and that the gene transcriptional effect of this activation is tightly regulated and depends on variables such as cellular context and experimental conditions. The C-terminal 29-amino acid difference between our sequence and the construct used by Parnell et al (7) may contain a regulatory domain determining Jun-ATF or Jun-Fos activation. Divergent mechanisms of AP-1 activation have been reported to be a major regulatory mechanism to determine the cellular response upon a certain stimulus (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that polycystin-1 is capable of inducing at least c-Jun and ATF2 activity and that the gene transcriptional effect of this activation is tightly regulated and depends on variables such as cellular context and experimental conditions. The C-terminal 29-amino acid difference between our sequence and the construct used by Parnell et al (7) may contain a regulatory domain determining Jun-ATF or Jun-Fos activation. Divergent mechanisms of AP-1 activation have been reported to be a major regulatory mechanism to determine the cellular response upon a certain stimulus (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…The protein level of c-Fos was not affected by the mouse C-terminal polycystin-1 construct, and activation of Jun-Fos dependent luciferase reporters was not detected under our experimental conditions. Parnell et al (7) have recently reported activation of a Jun-Fosspecific luciferase reporter using a construct containing the C-terminal 222 amino acids of mouse polycystin-1. We propose that polycystin-1 is capable of inducing at least c-Jun and ATF2 activity and that the gene transcriptional effect of this activation is tightly regulated and depends on variables such as cellular context and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the large size of native polycystin-1, we comparatively evaluated the gradient fractionation of a chimaeric, transmembrane form of the C-terminus of polycystin-1 that is known to be active in intracellular signalling [30][31][32]. The overexpressed C-terminus of polycystin-1 retained the ability to complex with flotillin-2 based on co-precipitation experiments ( Figure 4A).…”
Section: The Polycystin Multiprotein Complex Is Not Associated With Dmentioning
confidence: 99%
“…For example, PKD1 interacts with and activates heterotrimeric G i∕o proteins, potentially affecting diverse downstream signaling pathways (18)(19)(20)(21). On the other hand, TRPP2 interacts and forms functional heteromeric cation channels with other TRP channel subunits, including TRPC1 and TRPV4 (9,(22)(23)(24).…”
mentioning
confidence: 99%